2018
DOI: 10.3390/app8061009
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation on Performance of Compound-Modified Asphalt for Rock Asphalt/Styrene–Butadiene Rubber (SBR) and Rock Asphalt/Nano-CaCO3

Abstract: Abstract:As a natural modifier of asphalt, rock asphalt has been widely used to improve its thermal stability and aging resistance. However, the thermal cracking resistance of asphalt modified by rock asphalt is unsatisfactory. In order to improve the thermal cracking resistance in low temperature, two kinds of modifiers-styrene-butadiene rubber (SBR) and nano-CaCO 3 -were selected as the compound modifiers, and then implemented to improve the low-temperature performance of the binder. Then, compound asphalt m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The Dynamic Shear Rheometer (DSR) test can be conducted to determine the rheological behavior of asphalt binders in varying temperature and frequency conditions [40,41]…”
Section: Dynamic Shear Rheometer (Dsr) Testmentioning
confidence: 99%
“…The Dynamic Shear Rheometer (DSR) test can be conducted to determine the rheological behavior of asphalt binders in varying temperature and frequency conditions [40,41]…”
Section: Dynamic Shear Rheometer (Dsr) Testmentioning
confidence: 99%
“…The thermal cracking performance of 5% BRA/SBR-modified asphalt has been effectively improved, and that of nano-CaCO 3 was not obvious. Compound-modified asphalt mixtures have higher temperature stability, low-temperature cracking resistance, moisture susceptibility, and durability than 5% SBS modified asphalt [24][25][26].…”
Section: Introductionmentioning
confidence: 98%
“…Munzenberger et al obtained stress relaxation modulus from dynamic analysis by taking a nonlinear strain dependency of the viscoelastic properties into consideration and found that the Generalized Maxwell model could give results close to experimental data. The viscoelastic approach has also used in rubber‐blended building materials for creep evaluation with different constant temperatures . Yin et al performed time‐dependent tests on rubber specimens at room temperature and fit the test data using a number of viscoelastic models with conclusions that all the models were quantitatively equivalent.…”
Section: Introductionmentioning
confidence: 99%